Analisis Algoritma Pemrograman Dalam Media Sosial Terhadap Pola Konsumsi Konten - Amelia Tri Andini; Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Easy exploration of content - content containing videos or images on social media which in this case we as users do not know how the social media algorithm works in displaying the content we see. This research aims to analyze the influence of social media algorithms on content consumption patterns. This research uses a qualitative research method with a literature study research type and is continued by directly analyzing social media platforms, namely TikTok and Instagram. From the results of the analysis, it can be seen that the algorithm of this social media both on the TikTok and Instagram platforms has similarities, namely being influenced by interactions from users in the form of (likes, comments, and shares), user search history, trending topics, and influenced by accounts that are followed. So that the content consumption patterns of social media users will remain the same because all the content that users see or enjoy is based on the user's own interests.